Proteomics reveals the function reverse of MPSSS‐treated prostate cancer‐associated fibroblasts to suppress PC‐3 cell viability via the FoxO pathway. (11th March 2021) - Zhang, Tingting; Chen, Xiulan; Sun, Lang; Guo, Xiaojing; Cai, Tanxi; Wang, Jifeng; Zeng, Yanqiong; Ma, Jing; Ding, Xiang; Xie, Zhensheng; Niu, Lili; Zhang, Mengmeng; et al.
Abstract: Prostate cancer‐associated fibroblasts (prostate CAFs) are essential components of the tumor microenvironment and can promote tumor progression through their immunosuppressive functions. MPSSS, a novel polysaccharide purified from Lentinus edodes, has been reported to have anti‐tumor activity. MPSSS could also inhibit the immunosuppressive function of prostate CAFs, which has been demonstrated through that the secretome of MPSSS‐treated prostate CAFs could inhibit the proliferation of T cells. However, how the secretome of MPSSS‐treated prostate CAFs influence prostate cancer progression is still unclear. Interestingly, we found that the low molecular weight (3–100kD) secretome of prostate CAFs (lmwCAFS) could promote the growth of PC‐3 cells, while that of MPSSS‐treated prostate CAFs (MT‐lmwCAFS) could inhibit their growth. We carried out comparative secretomic analysis of lmwCAFS and MT‐lmwCAFS to identify functional molecules that inhibit the growth of PC‐3 cells, and proteomic analysis of lmwCAFS‐treated PC‐3 cells and MT‐lmwCAFS‐treated PC‐3 cells to investigate the underlying molecular mechanism. These analyses suggest that TGF‐β3 from MT‐lmwCAFS may inhibit the growth of PC‐3 cells. The validated experiments revealed that TGF‐β3 from MT‐lmwCAFS activated p21 expression in PC‐3 cells by regulating the FoxO pathway thereby inducing G0/G1 cell cycle arrest of PC‐3 cells. Overall, our data demonstrated that MPSSS reversed the ability of prostate CAFs to suppress the cell viability of PC‐3 cells, which might provide a potential therapeutic strategy to prevent prostate cancer progression. Abstract : MPSSS reversed the tumor‐promoting effect of prostate CAFs; TGF‐β3 was upregulated in MPSSS‐treated prostate CAFs to arrest the PC‐3 cells in G0/G1 phase via the FoxO pathway.